RANCANG BANGUN APLIKASI DASHBOARD MOBIL LISTRIK MENGGUNAKAN PROTOKOL BLUETOOTH BERBASIS ANDROID - , ASEP NUGRAHA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Vehicle instrument panel (dashboard) is the interface that connects the driver with electronic and mechanical systems of the vehicle. Dashboard provide information about vehicle speed, engine rpm, engine temperature , battery capacity (in electric vehicles) or remaining fuel in the tank (on oil-fueled vehicle). The current conventional dashboard, the majority are still analog and mechanical. This leads to lower levels of flexibility, difficult to change and upgrade over the instrument panels. Therefore, in the future, there will be migration from the use of mechanical and analog conventional dashboard, into a digital dashboard, which all the panels displayed on a screen or a liquid-crystal-display (LCD ). Android-based digital electric car dashboard is an Android-based digital dashboard application installed on Android-based tablet. Dashboard application is designed to replace the role of conventional dashboard and provide more interactive interaction to the driver. This application uses the SPP-Bluetooth protocol (serial-port-protocol) to be able to connect to the microcontroller-based electronic and mechanical systems of electric cars. The attributes of the instrument panel on the application can be configured in accordance with the wishes of the driver. The development of these applications using Java language that is able to accommodate the user needs to use the features of Android. Tools to support the development of applications are Android IDE (Eclipse, Android SDK, ADT), libraries and APIs support like Android Bluetooth API, shared preferences, and android.graphics. In order for two different devices, Android tablets and electronic systems can be connected and establish communication using Bluetooth, it is necessary to use standardized handshake protocol and standardized data format. Dashboard application testing use a Nuvoton ARM-based microcontroller electronic system. Potentiometers input data were transmitted from the electronic system to the dashboard application via Bluetooth protocol using a standardized data format. Once the data is parsed and processed by the application, the data is shown directly on the corresponding instrument panel. The results of the testing are dashboard application capable of receiving the potentiometers input data from electronic system via Bluetooth, converting data, and can display the right value on the instrument panel.